Expanding the clinical and immunological phenotypes of COPB1 deficiency - Alroqi, Fayhan; Algholaiqa, Thekra; Alajaji, Sulaiman; Altuwaijri, Abeer; Althubaiti, Nouf (Frontiers in Immunology, 2026)
PurposeCOPB1 encodes the coatomer subunit beta protein, which is essential for brain development and intracellular protein trafficking. Homozygous mutations cause Baralle–Macken syndrome that characterized by global developmental delay, severe intellectual disability, and early-onset cataracts. Although immunodeficiency has been observed in patients with COPB1 deficiency, the immunological phenotype remains incompletely characterized. Here, we comprehensively describe the clinical features and delineate the immunological phenotype associated with COPB1 mutations.MethodsWe performed detailed clinical and immunological evaluations of three female siblings with COPB1 deficiency. Flow cytometry was used to characterize lymphocyte subsets and to assess cytokine secretion following stimulation. Functional proliferation of peripheral blood mononuclear cells (PBMCs) was assessed using dye labeling, CD3/CD28 activation, and flow cytometric analysis.ResultsThree female siblings with COPB1 deficiency presented with early-onset cataracts, global developmental delay, hypotonia, and progressive spasticity leading to quadriplegia. All patients experienced recurrent infections beginning in early childhood. Immunological evaluation revealed neutropenia, T cell lymphopenia, profound reduction in switched and unswitched memory B cells, and absent specific antibody responses. All the three patients were initiated on immunoglobulin replacement therapy and antimicrobial prophylaxis.ConclusionOur findings expand the clinical and immunological spectrum of COPB1 deficiency, demonstrating combined immunodeficiency with neutropenia, lymphopenia and impaired specific antibody responses. These results support the classification of COPB1 deficiency as a combined immunodeficiency with syndromic features under the IUIS classification system and emphasize the importance of comprehensive immunological evaluation and early immunoglobulin replacement therapy in patients with COPB1 mutations.